A year in pharmacology: new drugs approved by the US Food and Drug Administration in 2020 - Kayki-Mutlu, Gizem (Naunyn Schmiedebergs Arch Pharmacol, 2021)
While the COVID-19 pandemic also affected the work of regulatory authorities, the US Food and Drug Administration approved a total of 53 new drugs in 2020, one of the highest numbers in the past decades. Most newly approved drugs related to oncology (34%) and neurology (15%). We discuss these new drugs by level of innovation they provide, i.e., first to treat a condition, first using a novel mechanisms of action, and “others.” Six drugs were first in indication, 15 first using a novel mechanism of action, and 32 other. This includes many drugs for the treatment of orphan indications and some for the treatment of tropical diseases previously neglected for commercial reasons. Small molecules continue to dominate new drug approvals, followed by antibodies. Of note, newly approved drugs also included small-interfering RNAs and antisense oligonucleotides. These data show that the trend for declines in drug discovery and development has clearly been broken.